A GENETIC LINKAGE MAP OF 35 POLYMORPHIC LOCI FOR THE LONG ARM OF HUMAN CHROMOSOME 3 - Wei, Minghui (My University, 1993)
To construct a high resolution genetic map of the long arm of chromosome 3q, 32 new RFLPs were identified by screening 555 single copy human chromosome 3 DNA fragments from two flow-sorted chromosome 3 libraries. One highly informative microsatellite, a CA dinucleotide repeat, was isolated from a cosmid library. The genotypes for 32 RFLP markers and 1 microsatellite marker were generated by hybridization to DNA from members of 59 Centre d'Etude du Polymorphism Humaine (CEPH) families and DNA amplification of 9 CEPH families using the polymerase chain reaction (PCR), respectively. Two point and multipoint linkage analyses were performed with the CRI-MAP program. The average heterozygosities of 32 RFLP markers and 1 microsatellite marker are 0.44 and 0.84, respectively. Twenty markers could be uniquely ordered at odds of at least 1000:1. The sex-averaged length of this map is 126.6 cM. The average distance between markers is 5.7 cM, and the largest interval between markers is 16.7 cM. The sex-specific map spans 168.6 cM in female and 95.8 cM in male, respectively. The distance ratio of the female to male map is 1.7. Analysis of sex-difference in recombination frequency reveals a significant difference, x²=89.5, P<0.05. Several intervals of excess male recombination were observed. This map will be useful in further efforts to develop the highest resolution map at a 1-2 cM interval, to localize genetic disease genes and to provide information for a complete physical map.